2018
DOI: 10.3389/fphys.2018.01622
|View full text |Cite
|
Sign up to set email alerts
|

Saxagliptin but Not Sitagliptin Inhibits CaMKII and PKC via DPP9 Inhibition in Cardiomyocytes

Abstract: Some oral anti-hyperglycemic drugs, including gliptins that inhibit dipeptidyl peptidase 4 (DPP4), have been linked to the increased risk of heart failure (HF) in type-2 diabetic patients. While the cardiovascular safety trial, TECOS, revealed no link between sitagliptin and the risk of HF, a substantial 27% increase in the hospitalization for HF was observed in type-2 diabetic patients treated with saxagliptin within the SAVOR-TIMI 53 trial. A previous in vitro study revealed that saxagliptin impairs the Ca2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…However, it cannot be excluded that it could also be associated with some property of the saxagliptin molecule, unrelated to its action as a DPP-4 inhibitor. Accordingly, in vitro and ex vivo studies have shown that exposure to saxagliptin (135, 136) but not sitagliptin (136), results in altered cardiac electrophysiology and is associated with impaired cardiomyocyte contractility. The mechanism has been suggested to involve inhibition of cardiac intracellular signaling pathways (Ca 2+ /calmodulin-dependent protein kinase II and protein kinase C) due to saxagliptin-mediated inhibition DPP-9 (136).…”
Section: Dpp-4 Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it cannot be excluded that it could also be associated with some property of the saxagliptin molecule, unrelated to its action as a DPP-4 inhibitor. Accordingly, in vitro and ex vivo studies have shown that exposure to saxagliptin (135, 136) but not sitagliptin (136), results in altered cardiac electrophysiology and is associated with impaired cardiomyocyte contractility. The mechanism has been suggested to involve inhibition of cardiac intracellular signaling pathways (Ca 2+ /calmodulin-dependent protein kinase II and protein kinase C) due to saxagliptin-mediated inhibition DPP-9 (136).…”
Section: Dpp-4 Inhibitorsmentioning
confidence: 99%
“…Accordingly, in vitro and ex vivo studies have shown that exposure to saxagliptin (135, 136) but not sitagliptin (136), results in altered cardiac electrophysiology and is associated with impaired cardiomyocyte contractility. The mechanism has been suggested to involve inhibition of cardiac intracellular signaling pathways (Ca 2+ /calmodulin-dependent protein kinase II and protein kinase C) due to saxagliptin-mediated inhibition DPP-9 (136). DPP-9 belongs to the same family as DPP-4, and it is known that saxagliptin is a less selective inhibitor, whereas sitagliptin is highly selective for DPP-4 (35) and does not alter DPP-9 activity (136).…”
Section: Dpp-4 Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…While DPP‐4 was predominantly expressed by coronary capillaries and immune cells, some cardiomyocytes also express DPP‐4 within the cytosol (Figure A; black arrows), as published previously 35,36 . Furthermore, gliptins (saxagliptin and sitagliptin) are internalized by cardiomyocytes and localize to the cytosol 37,38 . As such, we first investigated whether linagliptin could directly affect cardiomyocyte F passive in vitro in human cardiomyocytes in the absence of cardiometabolic risk factors.…”
Section: Resultsmentioning
confidence: 59%
“…Moreover, the structural differences of the compounds within the class of DPP4i are relevant for the treatment effect. Saxagliptin, but not sitagliptin, was shown to affect CaMKII/PLB phosphorylation in cardiomyocytes through off-target inhibition of DPP9, which leads to prolonged action potential duration and may trigger arrhythmic events (Koyani et al, 2018). These results indicate that off-target activities of DPP4i on other DPPs may contribute to the different outcome of DPP4i in the clinical trials.…”
Section: Direct Cardiac Effects Question the Molecular Targetmentioning
confidence: 88%